2020
DOI: 10.3390/su13010118
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the COVID-19 Emergency on Local Vehicular Traffic and Its Consequences for the Environment: The Case of the City of Reggio Emilia (Italy)

Abstract: The COVID-19 health emergency has imposed the need to limit and/or stop non-essential economic and commercial activities and movement of people. The objective of this work is to report an assessment of the change in vehicle flows and in air quality of a specific study area in the north of Italy, comparing the periods February–May 2020 and February–May 2019. Circulating vehicles have been measured at nine characteristic points of the local road network of the city of Reggio Emilia (Italy), while atmospheric pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 57 publications
3
22
0
Order By: Relevance
“…For other pollutants, the lockdown period caused an increase in pollutant concentrations, which was the opposite trend than in many other places around the world. For example, in [52] it was indicated that in the City of Buenos Aires the decrease in PM 10 and NO 2 concentration was about 30% each, in [53] it was reported that PM 2.5 concentration in Athens decreased by almost 20%, according to [54] in A Coruña and Vigo the concentrations decreased from 25% to 49% for PM 10 and from 10% to 38% for PM 2.5 , and in North Italy comparing the periods February-May 2020 to February-May 2019 the reduction in case of NO 2 was over 30% [55].…”
Section: Discussionmentioning
confidence: 89%
“…For other pollutants, the lockdown period caused an increase in pollutant concentrations, which was the opposite trend than in many other places around the world. For example, in [52] it was indicated that in the City of Buenos Aires the decrease in PM 10 and NO 2 concentration was about 30% each, in [53] it was reported that PM 2.5 concentration in Athens decreased by almost 20%, according to [54] in A Coruña and Vigo the concentrations decreased from 25% to 49% for PM 10 and from 10% to 38% for PM 2.5 , and in North Italy comparing the periods February-May 2020 to February-May 2019 the reduction in case of NO 2 was over 30% [55].…”
Section: Discussionmentioning
confidence: 89%
“…However, researchers have provided different explanations according to their understanding and based on the local meteorological and emission conditions. Donzelli et al [20], Marinello et al, [24] and Hormann et al [22] thought that people used the indoor heating system more frequently as they spent more time indoors during the lockdown, which increased PM emissions. They suggested further research to fully comprehend this matter.…”
Section: Relationship Between Air Pollutant Concentrations and Mobilitymentioning
confidence: 99%
“…In addition, they also mentioned that PM 10 values were unusually low in the control group. In addition, Marinello et al, [24] suggested that primary emissions, biomass combustion, PM precursors emissions, meteorological conditions, and the formation of secondary PM could have resulted in the high levels of PM during the lockdown period. Furthermore, industrial sources, harbour emissions, construction works, dust resuspension, regional air mass transport, and Saharan dust episodes could be responsible for the PM episodes [26].…”
Section: Relationship Between Air Pollutant Concentrations and Mobilitymentioning
confidence: 99%
“…Because of these severe changes in the everyday mobility of individuals, nonnegative effects on the urban environment were observed worldwide. First, significant reductions of pollutants produced by vehicles, in particular NO 2 and CO, were recorded in many countries [32] such as Brazil [33], China [34], France [35], Spain [36], Italy [37,38] and the United States [34]. Moreover, road accidents decreased in many cities [39], thereby lowering the number of fatalities [40].…”
Section: Introductionmentioning
confidence: 99%